2015
DOI: 10.1111/nph.13652
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of floral volatiles and pleiotropic responses to artificial selection in Brassica rapa

Abstract: SummaryThe evolution of the vast diversity of floral volatiles is little understood, although they serve fundamental functions, such as pollinator attraction and herbivore deterrence. Floral volatiles are often species specific, yet highly variable and sensitive to environmental factors. To date, nothing is known about the heritability of floral volatiles, and whether individual compounds can evolve independently or solely in concert with the whole volatile bouquet.We conducted bi-directional artificial select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(85 citation statements)
references
References 98 publications
5
79
0
1
Order By: Relevance
“…Evolutionary change in non-selected VOCs can be explained by pleiotropy or close linkage between individual “scent genes” (linkage disequilibrium). These mechanisms were previously suggested to contribute to the evolution of scent bouquets19. The transcriptome data of the high and low selection line plants render us the possibility to unravel the molecular mechanisms of these phenomena.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Evolutionary change in non-selected VOCs can be explained by pleiotropy or close linkage between individual “scent genes” (linkage disequilibrium). These mechanisms were previously suggested to contribute to the evolution of scent bouquets19. The transcriptome data of the high and low selection line plants render us the possibility to unravel the molecular mechanisms of these phenomena.…”
Section: Resultsmentioning
confidence: 83%
“…19. 50 seeds from ten individuals (5 seeds per each mother plant) of third generation plants for both “high” and “low” selection lines were sown out in standardized soil (Humuswerke Gebr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As with other floral traits, floral scents are known to vary within species, both within and among populations (Dötterl et al 2005;Chartier et al 2013;Mant et al 2005;Stökl et al 2009;Sun et al 2014), and this variability is strongly suggested to have a genetic basis (e.g., Andargie et al 2014;Friberg et al 2013;Zu et al 2016). However, little is known whether such genetic variability is the result of divergent selection or other scenarios (e.g., drift).…”
Section: Such Variations In Floralmentioning
confidence: 99%
“…In Antirrhinum the gene COMPACTA is involved in maintenance of B function affecting petal size and scent emission (Manchado-Rojo et al, 2012). A study of narrow sense heritability in Brassica rapa has shown that although scent profiles between species differ in many cases in a number of independent VOCs, they may have coregulation between them and with other morphological traits or flowering time (Zu et al, 2016). The genes involved in single compound biosynthesis together with regulatory loci with several genetic functions indicates that the natural variation of scent emission may identify both regulatory loci as in Petunia and structural genes involved in discrete VOCs biosynthesis, or form part of larger pathways, affecting downstream products.…”
Section: Introductionmentioning
confidence: 99%